FINANCIAL RATIO ANALYSIS TO MEASURE FINANCIAL PERFORMANCE OF PT. MEKATAMA SON'S WORKS IN THE 2018-2022 PERIOD - Kairul Nisa; Abdul Muttalib; Abdul Salam (CV. AFDIFAL MAJU BERKAH, 2024)
The aim to be achieved in this research is to determine the effectiveness and efficiency of financial performance measured by the level of efficiency ratios and activity costs and profitability. The sample in this research is the balance sheet and profit and loss report of PT. Putra Mekatama's work in the Gowa area for the 2018-2022 period. This research uses a quantitative approach, which is based on the philosophy of potivism and is used to investigate certain populations or samples. Based on the results of the analysis of efficiency and effectiveness ratios over the last 5 years, it shows that for this type the average operational cost ratio is 6.01%, the average cost of goods sold ratio is 0.86%, the average sales cost ratio per year is 3.51% administrative cost ratio of 6.5%, financial cost ratio of 0.81%, average gross profit margin ratio of 0.14%, and net profit margin ratio (gross profit margin) an average of 0.37%.